Best proximity points of α-β-ψ-proximal contractive mappings in complete metric spaces endowed with graphs - Suthep Suantai (2020)
© 2019 Kyungnam University Press. In this work, we present the notion of an α-β-ψ-G-proximal contraction in metric spaces endowed with graph. We investigate the existence and uniqueness of best proximity points for this modified contractive mapping. The results obtained extended and generalized some fixed and best proximity points results in literature. Examples are given to validate the main results.